Successful Aging and Quality of Life among Filipino LGBT Older Adults: The Moderating Role of Resilience - Gaddi, John Angelo B.; Guintu, Ma. Agatha Anne D. (Future Science / FSH-PH Publications, 2025)
The critical role that successful aging has played on human beings to living fulfilling and meaningful lives in the midst of trials and tribulations is fast becoming noticeable. Nonetheless, there seems to be an undeniable gap in prior studies that investigates at what constitutes successful aging amongst adults in the LGBT spectrum, not to mention in the Philippine setting with its own particular cultural and social milieu. The study at hand explores the connection between successful aging and quality of life and to see whether resilience moderates such relationship amongst older adults in the LGBT group. Data were gathered from 164 respondents aged 55 and above through convenience sampling. Open-access instruments were used for this study including the Successful Aging Scale, the WHO Quality of Life–BREF (Filipino version), and the Brief Resilience Scale. Correlation and regression analyses were then performed in the study. Results showed a significant positive correlation between successful aging and quality of life (r = 0.55, p < 0.0001). Furthermore, moderation analysis revealed that resilience enhanced this relationship (b = 0.14, SE = 0.04, p = 0.0005). This shows the significant role of resilience as an important psychological resource that improves the favorable and positive impact of successful aging towards quality of life on Filipino LGBT older individuals.